2011
DOI: 10.12681/mms.37
|View full text |Cite
|
Sign up to set email alerts
|

Effect of twine thickness on selectivity of gillnets for bogue, Boops boops,in Turkish waters

Abstract: To investigate the effect of twine thickness on the selectivity of multifilament gillnet targeting bogue,Boops boops L., four different stations were sampled between March and November 2008 in the northern Aegean Sea. Gillnets with 22, 23, and 25 mm nominal mesh size (bar length) each having two different twine thicknesses (approximately 0.45 mm and 0.54 mm ∅) were applied for this purpose. The deviances from the SELECT method revealed that lognormal models provided the best fits for both of the twine thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…It is practically accepted that the diameter and material of twine can influence visibility, elasticity and flexibility of both gillnet and trammel net (Balık & Çubuk, 2000;Holst et al, 2002). Typically, monofilament is more elastic and more efficient than multifilament due to smaller twine diameter (Karlsen & Bjarnason, 1986, Ayaz et al, 2011 and is less visible (Backiel & Welcomme, 1980;Radhalakshmi & Gopalan Nayar, 1985) explaining the primary differences in efficiency between these twine materials. Thus, the catching efficiency of monofilament trammel nets is higher than multifilament for catching fish species (Wudianto et al, 1988;Balik, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is practically accepted that the diameter and material of twine can influence visibility, elasticity and flexibility of both gillnet and trammel net (Balık & Çubuk, 2000;Holst et al, 2002). Typically, monofilament is more elastic and more efficient than multifilament due to smaller twine diameter (Karlsen & Bjarnason, 1986, Ayaz et al, 2011 and is less visible (Backiel & Welcomme, 1980;Radhalakshmi & Gopalan Nayar, 1985) explaining the primary differences in efficiency between these twine materials. Thus, the catching efficiency of monofilament trammel nets is higher than multifilament for catching fish species (Wudianto et al, 1988;Balik, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Practically trammel net or gillnet with the same nominal mesh sizes but different twine thicknesses will possibly result in different mesh openings during the fishing operation. Ayaz et al (2011) investigated the effect of twine thickness on the selectivity of multifilament gillnet when targeting Bogue (Boops boops L), and found that the 22 mm mesh size net (0.45 mm ) captured significantly larger fish than the 23 mm mesh size net (0.54 mm ), due to the higher elasticity and flexibility of the thinner twine. Park et al (2011) found that the size selectivity of the trammel net and gillnet was significantly different with only 0.2 cm difference in the modal length.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, results are similar because of the similar study areas. In addition, the results are compared with Ayaz et al (2011), there are differences among the modal lengths for 44 and 50 mm mesh sizes (23.31 and 26.41 cm modal length) due to the seasonal differences. However, we cannot compare the effect of hanging ratio on selectivity with this study because of different the hanging ratios.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkish waters selectivity studies are mainly related to gillnet (e.g. Özekinci, 2005; Aydın & Düzgüneş, 2007; Karakulak & Erk., 2008; Ayaz et al ., 2011). However, gillnet selectivity studies in the Black Sea are limited to a few species such as red mullet ( Mullus barbatus ) (Genç, 2000; Dinçer & Bahar, 2008) and whiting (Aydın, 1997; Genç et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%